Neuronal activity inhibits mitochondrial transport only in synaptically connected segments of the axon - Venneman, Tom; Vanden Berghe, Pieter (Frontiers in Cellular Neuroscience, 2024)
Due to their large scale and uniquely branched architecture, neurons critically rely on active transport of mitochondria in order to match energy production and calcium buffering to local demand. Consequently, defective mitochondrial trafficking is implicated in various neurological and neurodegenerative diseases. A key signal regulating mitochondrial transport is intracellular calcium. Elevated Ca2+ levels have been demonstrated to inhibit mitochondrial transport in many cell types, including neurons. However, it is currently unclear to what extent calcium-signaling regulates axonal mitochondrial transport during realistic neuronal activity patterns. We created a robust pipeline to quantify with high spatial resolution, absolute Ca2+ concentrations. This allows us to monitor Ca 2+ dynamics with pixel precision in the axon and other neuronal compartments. We found that axonal calcium levels scale with firing frequency in the range of 0.1 -1 µM, whereas KCl-induced depolarization generated levels almost a magnitude higher. As expected, prolonged KCl-induced depolarization did inhibit axonal mitochondrial transport in primary hippocampal neurons. However, physiologically relevant neuronal activity patterns only inhibited mitochondrial transport in axonal segments which made connections to a target neuron. In 'non-connecting' axonal segments, we were unable to trigger this inhibitory mechanism using realistic firing patterns. Thus, we confirm that neuronal activity can indeed regulate axonal mitochondrial transport, and reveal a spatial pattern to this regulation which went previously undetected. Together, these findings indicate a potent, but localized role for activity related calcium fluctuations in the regulation of axonal mitochondrial transport.